Correlación entre el Gasto Público en Educación y los logros de Aprendizaje de los estudiantes de nivel primario de las Instituciones Educativas pertenecientes al programa estratégico logros de Aprendizaje al finalizar el III ciclo de Educación Básica regular de la Provincia de San Martín, periodo 2009 - 2012 - León Mestanza, Cecilia Del Pilar (2014)
Education is one of the most important factors of economic growth. Certainly the public expenditure on education has generally supported by most modern societies. In Peru, spending on education is substantial and growing. So the purpose of this research is to investigate the degree of correlation between public spending on education and learning achievements under the Strategic Achievements Learning Program in the province of San Martín for the period 2009-2012. According to the technique of contrasting, this research is correlational; because it explains the relationship between the independent variable, public spending on education; and the dependent variable, learning achievement, through the coefficient of determination. For research, the scientific method was used in its analytical – synthetic form; in order to consider each document as a unit of analysis and work path synthesize information that is relevant to consider to achieve our goals. As a result there has not been found a significant correlation between public spending on education and achievement of students learning at the primary level educational institutions in the Achievements Strategic Learning Program at the end of the third cycle of Basic Education in the province of San Martín, for the study period 2009 – 2012 These findings are backed by a 95 percent confidence level and 5 percent level of significance, with probabilities of success and failure 50 percent respectively.